Students’ Speaking Ability at Ninth Grade of Junior High School Number 6 Jambi City - Mia Fadila; Efa Silfia; Ridho Praja Dinata (Universitas Batanghari Jambi, 2022)
This research was conducted with the aim of to know students’ speaking skills, especially in the component of speaking skills in the ninth grade of Junior High School 6 Jambi City. This research was designed using descriptive quantitative research methods. The population of this study was the ninth-grade students at Junior High School 6 Jambi City, and the sample was grade IX B students. This study uses a test as a research instrument. Then the test results are assessed. The test used is an oral test. The oral test is made with the theme of